Trunk strength and range of motion in adolescent basketball, soccer and tennis players with and without low back pain history - Vatovec, R.; Kozinc, Ž.; Sarabon, N. (German Journal of Exercise and Sport Research, 2023)
The role of trunk strength and range of motion (RoM) in low back pain (LBP) risk in athletes is still unclear. The purpose of this study was to compare trunk muscle strength and RoM in adolescent athletes with and without LBP (total n= 381; age= 16.5± 2.1 years). The participants included basketball, soccer and tennis players who currently participate in normal training/competition regimen, have regularly participated in training for >3 years (mean: 7.2± 3.2 years) and perform at least 4 training sessions in their sport per week (mean: 6.1± 1.2 sessions/week). The participants performed isometric trunk extension, flexion and lateral flexion strength assessments, as well as RoM tests (Schober`s test, lateral flexion RoM) and reported the 1-year LBP history. Female basketball players with LBP history had lower lateral flexion RoM than their LBP-free counterparts (relative difference= 11.3-12.7%; p= 0.022-0.043), while the opposite was the case in the male tennis subgroup (relative difference= 9.7-14.1%; p= 0.027-0.032). Trunk flexion RoM was 24-28% greater in athletes with LPB cases that required absence from training/competition in female subgroups (p= 0.018-0.23). In male tennis players, absolute and body-mass-normalized trunk extension strength were 51-63% lower in athletes with LPB cases that required absence from the training and competition (p= 0.016-0.027). Further prospective studies are needed, as our study could not clearly elucidate the effect of trunk strength and RoM on LBP risk in adolescent athletes.